Publicity of planning documentation as a prerequisite for effective public control of urban systems development - Medynska, N. (Land Management, Cadastre and Land Monitoring, 2017)
Nowadays, government transparency is one of the fundamental principles of functioning of the rule of law, in which participation of the public in the formulation and implementation of public policy and its impact on all stages of decision-making and public access to the full objective and reliable information held by authorities should be provided. The interaction with the public is a key in the Association Agreement between Ukraine and the European Union, which is prepared to the signing and implementation. Ukraine moves to decentralization, and the main problem is to optimize the structure of administrative units, which are characterized by high fragmentation, especially in rural areas. Most rural councils are unable to provide even basic services to the local population at the district level. This leads to a decrease in financial resources of village councils. Decentralization of authority will enable administrative-territorial units to become more self-sufficient, provide fiscal autonomy, the distribution of income and expenditure, a clear division of authorities’ competences. This particularly touches rural areas that are now largely depressed administrative entities. Local interests may be assessed much better by local authority than central. The order of publication of regulatory and urban acts is arranged by applicable law quite well and logically. Therefore, it can be similarly applied to all other legal acts. As every planning document, the community territory plan is approved by the local government, but should be developed by a certified institution, organization. This plan should provide answers to the question: what is the situation now; the current and future land-use, what are the prospects of development of the community in land management. Community management has the right and even the duty to decide on changes in the plan. Because in this plan will be shown in reality how and which way you can change the intended land-use. Territorial communities can attract investors when they will have a transparent system of land-use. To do this, there should be a legislation act, which provides the right to manage land throughout the jurisdiction of the unified local community, established under the long-term plan and with the approval of the planning documents for the respective territory of the community There is an urgent need for appropriate changes to the Land Code and adoption of transfer of land ownership from one form to another, which should reflect the European countries’ practice in the field. Keywords: decentralization, general plan, planning documentation, local governments, public information.